The Effect of Silent Sitting and Learning Motivation on the Learning Behavior of Buddhist Students at SMP Insan Teratai During the Covid-19 Pandemic - Mi, Nio She; Utomo, Budi; Kabri, Kabri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study explores the relationship between a quiet environment and learning motivation on the academic performance of SMP Insan Teratai students during the COVID-19 pandemic. This study uses a descriptive quantitative approach with a saturated sampling method involving 42 Buddhist students as respondents. Data was collected through a closed survey and analyzed using simple regression, multiple regression, classical statistical tests, and t-test techniques. The results showed that silent sitting and learning motivation affected students' learning behavior by 28.10% and 53.47%, respectively, simultaneously having an effect of 55.8%. It is proven that improving students' learning behavior can be achieved through a calm atmosphere and increased learning motivation.